2020
DOI: 10.1111/cts.12893
|View full text |Cite
|
Sign up to set email alerts
|

DDGP vs. SMILE in Relapsed/Refractory Extranodal Natural Killer/T‐cell Lymphoma, Nasal Type: A Retrospective Study of 54 Patients

Abstract: Extranodal natural killer/T-cell lymphoma, nasal type (ENKL) is a rare peripheral T-cell lymphoma that predominantly occurs in Asian and South American populations. The treatment of ENKL has been a challenge for a long time. This study was conducted to compare the clinical efficacy and safety of cisplatin, dexamethasone, gemcitabine, and pegaspargase (DDGP) and methotrexate, dexamethasone, ifosfamide, L-asparaginase, and etoposide (SMILE) regimens for relapsed/refractory ENKL and explore the prognostic factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…The 1-year PFS was also higher for DDGP (86%) than for SMILE (38%), p = 0.006. The DDGP regimen showed better tolerability, less leukopenia ( p = 0.030) and less allergic reactions ( p = 0.015) 21 . In opposition, SMILE was associated with higher rate of grade 3/4 adverse events, including diarrhea, mucositis, heart failure, arrhythmias and deaths related to treatment 21 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The 1-year PFS was also higher for DDGP (86%) than for SMILE (38%), p = 0.006. The DDGP regimen showed better tolerability, less leukopenia ( p = 0.030) and less allergic reactions ( p = 0.015) 21 . In opposition, SMILE was associated with higher rate of grade 3/4 adverse events, including diarrhea, mucositis, heart failure, arrhythmias and deaths related to treatment 21 .…”
Section: Discussionmentioning
confidence: 97%
“…The tumor cells of the ENKTL present high P-glycoprotein (Pgp) concentration, which confers a multidrug resistant (MDR) phenotype and resistance to anthracycline-based regimens, the most used treatment in clinical practice for mature T-cell lymphomas 4 , 15 , 16 . Chemotherapy agents attempting to overcome MDR mechanisms such as platinum analogues, ifosfamide, etoposide and asparaginase have demonstrated better responses and improved outcomes when compared to anthracyclines 17 21 . Since ENKTL is highly sensitive to radiation, high-dose extended-field radiotherapy (EF-RT) with 50–60 Gy has become a backbone for treatment of early-stage disease 17 , 22 , 23 .…”
Section: Introductionmentioning
confidence: 99%
“…The regimen DDGP (dexamethasone, gemcitabine, cisplatin, and pegylated asparaginase) had been compared prospectively and retrospectively with SMILE. Results purportedly showed that DDGP led to better CR and survivals [ 76 , 77 ]. However, these studies were seriously flawed, because the outcomes of the SMILE cohorts were exceptionally poor, which accounted for the apparent but probably erroneous superiority of the DDGP regimen.…”
Section: Management Of Stage Iii/iv Nasal Nk/t-cell Lymphomasmentioning
confidence: 99%
“…However, severe adverse events remain an obstacle in clinical practice. Earlier investigations have indicated that approximately 70% of patients with ENKTL experience severe leukopenia (grades 3–4), leading to poor tolerance to treatment [ 29 , 30 ]. Therefore, low-toxicity chemotherapy with radiotherapy, such as RT and a two-thirds dose of DeVIC (dexamethasone, etoposide, ifosfamide, and carboplatin) chemotherapy (RT-2/3DeVIC), CCRT-VIDL (etoposide, ifosfamide, dexamethasone, and L-asparaginase), and RT-P-GEMOX, is applied to the treatment of adult ENKTL [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%